ANALISIS TINGKAT KEPUASAN KONSUMEN PADA RUMAH MAKAN PADANG DI DESA BALUNIJUK KABUPATEN BANGKA - Barus, Solydeo Isadora; Sitorus, Rostiar (Lampung University, 2024)
This research aims to describe the consumer characteristics and analyze the level of customer satisfaction. This research was conducted in August 2023 in Balunijuk Village, Merawang District, Bangka Regency. The method used in this research is purposive sampling. The data collection methods used in this research are observation, questionnaire, and interview. The data analysis method uses quantitative descriptive statistics and Customer Index Satisfaction (CSI) analysis with a Likert scale. The results of the study show that the consumer characteristics at Putra Minang restaurant and Minang Maimbau restaurant are predominantly students aged 18-21 years, female, have pocket money per month of less than Rp.1.000.000, come from Bangka Belitung University, live in boarding houses and reside in Balunijuk Village. The CSI calculation results at Putra Minang restaurant are 80.53% and at Minang Maimbau restaurant are 79.81% at the satisfied level.